Chronic diseases and depressive symptoms in China: a psychosocial mechanism perspective - Xu, Qingqing; Shang, Ruizhe; Jiang, Xia (Frontiers in Public Health, 2025)
IntroductionAlthough the co-morbidity of chronic diseases and depression has been widely documented, its psychosocial mechanisms have not been systematically explored. This study analyzed the impact of chronic disease on depression, while emphasizing the mediating roles that income satisfaction, job safety satisfaction, and social cognitive capital play in the psychosocial mechanism.MethodsUsing the 2022 China Family Tracking Survey (CFPS) data, this study conducted a baseline regression using an ordered logit model, and explored the pathways of chronic illnesses on depressive symptoms through mechanism tests and heterogeneity analyses (n = 7,896).ResultsChronic conditions are associated with a considerable increase in the risk of depressive symptoms (OR = 1.671, p < 0.01). Mechanistic analyses showed that income satisfaction, job safety satisfaction and social cognitive capital all played partial mediating roles. Heterogeneity analyses indicated that the impact of chronic illness on depression was stronger among males, individuals with less robust social support, and non-users of the Internet.DiscussionThis research reveals that chronic illness constitutes a notable risk factor for depression and underscores its indirect impacts on mental health through three psychosocial pathways: financial strain, job safety, and insufficient interpersonal trust. The results emphasize the importance of integrating socioeconomic support, workplace improvement and digital health resources in chronic disease management to mitigate the risk of depression.